Pengaruh Promosi, Harga Dan Kepercayaan Terhadap Kepuasan Konsumen Pada Toko Isna Collection Di Raman Utara - Yateno, Yateno; Fuadi, Selamet; Wardani, Yunita Setiyo (Universitas Muhammadiyah Metro, 2023)
Consumer satisfaction is an effort to maintain customers. For this reason, entrepreneurs mustfurther improve the performance and quality of their products so that consumers feel satisfiedand become customers for a long time. The formulation of the problem in this study is